Attitudes toward COVID-19 disease and vaccination in Hungary: A comparison of nurses and health workers against non-health workers - Annamária Pakai; Amira Mohammed Ali; Mohammed ALBashtawy; Miklós Zrínyi; Ilona Karácsony; Ibrahim Ayasreh; Rana Abdelfattah Al Awamleh; Haitham Khatatbeh (Tehran University of Medical Sciences, 2023)
Background & Aim: Hungary started to administer several COVID-19 vaccines; however, attitudes toward COVID-19 and vaccination are still poorly understood. This study aimed to explore how the attitudes toward COVID-19 disease are associated with the attitudes toward COVID-19 vaccination in Hungary and compare the attitudes of health and non-health workers toward COVID-19 disease and vaccination in Hungary. Methods & Materials: Using a descriptive, cross-sectional design, we recruited a sample of 1820 persons through an electronic survey. In addition to the sociodemographic questions, the attitudes towards COVID-19 disease and vaccination were assessed through self-developed, literature-based questionnaires. Principal component analysis, Spearman's correlation, linear regression, and the Mann-Whitney test were used in the data analysis. Results: The mean age for the study participants (n=1735) was 43.8 ± 6.2 years, and females were the majority (84.6%). Overall, participants showed good attitudes toward COVID-19 disease (mean score= 3.48, SD= 0.43) as compared to their attitudes toward COVID-19 vaccination (Mean score= 2.67, SD=  0.44). A positive correlation was found between the attitudes toward COVID-19 disease and attitudes toward vaccination in Hungary (r= 0.247, p< 0.01). Nurses and other health workers showed more positive attitudes toward COVID-19 vaccination than non-health workers. Conclusion: Hungarian decision-makers should intervene to improve the public's willingness to be vaccinated against COVID-19 or future pandemics. Health workers' knowledge and positive attitudes should be utilized in the media to encourage the general population to be vaccinated. The suggested questionnaires need to be validated for future pandemics' use.